The mechanisms of entry of scientific, industrial and educational institutions in the Povolzh’e rye cluster - O. V. Kostenko (Аграрная наука Евро-Северо-Востока, 2017)
Analysis of the branches of Russian agro-industrial complex making production and processing of winter rye has shown that there are definite prospects for growth of market for rye and products of its processing. Specificity of the vertical and horizontal economic relations testifies in favor to use the cluster approach for development of rye complex. As a pre-conditions for forming of inter-regional rye cluster on a territory of Privolzhsky federal district it may be called: highly expressed concentration of rye grain production with formed orientation to inter-regional markets; large amount of enterprises involved in all parts of technological chain of winter rye; high share of Russia in world rye production (20%) as a basis for possible orientation on world markets of winter rye’s grain and products of its processing; existence of results of scientifical research in almost all links of the cluster’s technological chain that may form the basis for cost reduction and (or) increase the demand for products of cluster’s enterprises. As a basic mechanisms for enterprises and organizations to participate in the rye cluster it can be used direct contacts between organizations within the cluster, the establishment (selection) of the organization - the cluster manager and cluster's initiative. Organizations who in 2013 established the Coordinating Council of the cluster can make a cluster initiative. It will be academic institutions leading in research on rye breeding, cultivation technologies and processing of winter rye as well as higher education institutions interested in participation in the rye’s cluster. It is also important to involve leading enterprises - large agricultural enterprises, flour mills, bakeries, pastry factories - at the stage of cluster initiative.